Aplicabilidade, habitabilidade e sustentabilidade da alvenaria com bloco de concreto aparente em instituições de ensino - Trajano, Michelle Daiany da Conceição (2016)
Masonry is considered an advantageous and good economic performance alternative, reducing the large volumes of waste and the use of other materials (steel, wood and coatings). This system is widely used in building houses, commercial and residential buildings, however, its use in buildings for educational purposes is less common. The aim of this study was to analyze the masonry with concrete blocks from the user point of view, in order to verify the applicability of processes, sustainability and livability of the building built with rationalization of the stages of the t educational environment construction. The case study, State School Garden Marisa, in Campinas (SP), had its performance verification process analyzed in situ, with data collection conducted through questionnaires with users, teachers, staff and students, as well as verification of the sensitivity of users regarding comfort in the use of the building in the morning and afternoon, from 08:00 to 12:00 and 14:00 to 17:30. In addition to field research, we used bibliographical research, interviewing techniques and photographic records, all guided by ethical aspects as determined in legislation. After the investigation of this process through field research and literature review, it was concluded by the good applicability, livability and sustainability of masonry with exposed concrete block in the educational institution under study. The completion of the work indicates factors related to masonry design with exposed concrete blocks and building as a whole, leading to success in performance verified in the case study.